2020
DOI: 10.1039/d0bm00427h
|View full text |Cite
|
Sign up to set email alerts
|

An engineered exosome for delivering sgRNA:Cas9 ribonucleoprotein complex and genome editing in recipient cells

Abstract: CRISPR-Cas9 components delivered by engineered exosomes achieve genome editing in recipient cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 38 publications
2
106
0
Order By: Relevance
“…Guidance of signature sequence In this method, also called active loading, mRNA can be entrapped into the exosomes by employing some helper proteins. As we know, some proteins enable to bind to specific RNA sequences, Packaging of mRNA inside exosome can be easily guided through the fusion of the structural and specific proteins of exosome and creating an engineered cell [101,102]. This method increases the efficiency of mRNA loading into the exosome [97].…”
Section: Exosome Loadingmentioning
confidence: 99%
“…Guidance of signature sequence In this method, also called active loading, mRNA can be entrapped into the exosomes by employing some helper proteins. As we know, some proteins enable to bind to specific RNA sequences, Packaging of mRNA inside exosome can be easily guided through the fusion of the structural and specific proteins of exosome and creating an engineered cell [101,102]. This method increases the efficiency of mRNA loading into the exosome [97].…”
Section: Exosome Loadingmentioning
confidence: 99%
“…CD63 cDNA was amplified and cloned into the pEGFP‐N1 vector (Addgene, MA, USA) as described previously (Ye et al., 2020). Then, plasmid for CD63‐EGFP expression was transfected into cells.…”
Section: Methodsmentioning
confidence: 99%
“…108 Another study found that sgRNA and Cas9 (although not Cas9 mRNA) can be packaged into exosomes and form a functional sgRNA:-Cas9 RNP complex, which can be delivered to target cells. 109 The researchers also engineered a modified exosome by fusing CD63, a membrane protein often found on exosomes, with GFP and used GFP nanobody-fused Cas9 since it readily binds with the CD63-GFP for more efficient loading of sgRNA:Cas9 RNPs into the exosome. The modified exosome delivered larger quantities of sgRNA and Cas9 proteins without altering the exosome morphology or the function of the CRISPR-Cas9 system and successfully removed the stop sequence in A549 cells containing stop-DsRed sequences, resulting in greater red fluorescent signals than their unmodified counterparts.…”
Section: Delivering Rna Therapies To the Cf Lung Is Challengingmentioning
confidence: 99%